Eco-friendly synthesis, characterization, in vitro and in vivo anti-inflammatory activity of silver nanoparticle-mediated Selaginella myosurus aqueous extract - Belle Ebanda Kedi P (Dove Medical Press, 2018)
Philippe Belle Ebanda Kedi,1,2 Francois Eya’ane Meva,3 Lebogang Kotsedi,2,4,5 Edwige Laure Nguemfo,6 Calvin Bogning Zangueu,1 Agnes Antoinette Ntoumba,1 Hamza Elsayed Ahmed Mohamed,2,4 Alain Bertrand Dongmo,1 Malik Maaza2,4 1Department of Animal Biology and Physiology, Faculty of Science, University of Douala, Douala, Cameroon; 2Nanosciences African Network (NANOAFNET), iThemba LABS-National Research Foundation, Somerset, South Africa; 3Department of Pharmaceutical Sciences, Faculty of Medicine and Pharmaceutical Sciences, University of Douala, Douala, Cameroon; 4UNESCO-UNISA Africa Chair in Nanosciences-Nanotechnology, College of Graduate Studies, University of South Africa, Pretoria, South Africa; 5Department of Physics, University of the Western Cape, Bellville, Cape Town, South Africa; 6Department of Biological Sciences, Faculty of Medicine and Pharmaceutical Sciences, University of Douala, Douala, Cameroon Introduction: There is emerging interest in medicinal plants in the biomedical field, due to their multitude of chemicals which show anti-inflammatory, antimicrobial, antiviral, or antitumoral potential. Research on medicinal plants has shown that nanotechnology could offer new solutions in the quality control, delivery aspects, or in sustaining herbal biological activities. This work reports on the preparation and characterization of silver nanoparticle-mediated Selaginella myosurus plant extract. Methods: Ultraviolet-visible spectroscopy, Fourier transform infrared spectroscopy, powder X-ray diffraction, energy dispersive X-ray spectroscopy, high-resolution scanning electron microscopy, high-resolution transmission electron microscopy, and selected area electron diffraction have been used to characterize the prepared silver nanoparticles. The synthetic stability was studied by varying concentrations and pH of reactants. Egg albumin denaturation and carrageenan-induced rat paw edema model were used to ascertain the anti-inflammation. Results: Ultraviolet-visible spectroscopy gave plasmon resonance ranging between 420 and 480 nm while Fourier transform infrared spectroscopy proved nano interface functionalized with organics. The powder X-ray diffraction pattern is in agreement with silver and silver chloride nanoparticles of crystallite size 33.7 nm and 44.2 nm for silver and silver chloride, respectively. Energy dispersive X-ray spectroscopy enables elemental characterization of the particles consisting of silver and silver chloride among main elements. Spherical silver grain of 58.81 nm average size has been depicted with high-resolution scanning electron microscopy and high-resolution transmission electron microscopy. Inhibitions of 99% and 60% were obtained in vitro and in vivo, respectively. Conclusion: The albumin denaturation and carrageenan-induced rat hind paw edema model to assess the anti-inflammatory potential of generated nanoparticles suggests that the silver nanoparticles may act as reducing/inhibiting agents on the release of acute inflammatory mediators. Hence, this work clearly demonstrated that silver nanoparticles mediated-Selaginella myosurus could be considered as a potential source for anti-inflammatory drugs. Keywords: eco-friendly synthesis, silver nanoparticles, Selaginella myosurus, anti-inflammatory